Factors affecting in milk composition in Cyprus , Local goats and their cross - مهدي العزاوي, زيد محمد; سعيد, سعد ابراهيم; ندا, سعد محمد (Journal of Kerbala for Agricultural Sciences, 2015)
This study was carried out in the station of ruminant research of the State Board for Agriculture Research, Ministry of Agricultural in Abu Ghraib (23 km west of Baghdad) for the period of 1/10/2012 - 25/9/2013. The objective of the present study was to study of fixed factors(Genetic group,typ of birth,sex of birth,month of birth,age of ewe and lactation of period) in some of milk composition (fat,protein and lactos%) in Cyprus , Local goats and their cross. The General linear model (GLM) within the SAS (2004) computer package was used to analyze the data. The study included 593 records for percentage of milk composition (fat,protein and lactose) of 119 goats. The overall means for the percentage of fat, protein and lactose were 2.98,2.98,4.44%, respectively. The resulted showed that all of environment factors are non- significant effect in protein percentage,wihle month of birth , age of goat and lactation stage are significant effect (P<0.05) for genetic groups. Month of birth was significant (P<0.05) and typ of birth was highly significant effect (p< 0.01) on lactose percentage , Also, regression of fat percentage on goat weight at birth was highly significant (p< 0.01) and non- significant of protein and lactose. Key words : milk composition , Cyprus . Local , goats